2016
DOI: 10.1016/j.jcmg.2016.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Dysautonomia Predicts Long-Term Survival in Hereditary Transthyretin Amyloidosis After Liver Transplantation

Abstract: Evaluation of cardiac dysautonomia is a valuable addition for predicting survival of mATTR patients following LT. Among the different techniques that evaluate cardiac dysautonomia, -MIBG scintigraphy and heart rate response to atropine had better prognostic accuracy. Multivariate models did not improve significantly prediction of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 35 publications
0
37
0
1
Order By: Relevance
“…The principle of autonomic dysfunction and interpretation of 123 I-MIBG scintigraphy in ATTRm patients is rather difficult to understand. 40,41 Sympathetic denervation and heart failure seem to coincide and contribute to each other, especially in advanced stages of the disease. 42 However, a recent study of Piekarski et al showed that 48% of asymptomatic patients show abnormal 123 I-MIBG findings whereas no cardiac uptake on 99m Tc-DPD scintigraphy is visible.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of autonomic dysfunction and interpretation of 123 I-MIBG scintigraphy in ATTRm patients is rather difficult to understand. 40,41 Sympathetic denervation and heart failure seem to coincide and contribute to each other, especially in advanced stages of the disease. 42 However, a recent study of Piekarski et al showed that 48% of asymptomatic patients show abnormal 123 I-MIBG findings whereas no cardiac uptake on 99m Tc-DPD scintigraphy is visible.…”
Section: Discussionmentioning
confidence: 99%
“…75 In a monocentric cohort study of 215 ATTRm amyloidosis patients, predictors of death were PND score > II, orthostatic hypotension, NYHA stage > I, QRS duration >120 ms, and thickened interventricular septum. 91 In a study of 116 patients with ATTRwt amyloidosis, reduced serum TTR values were associated with short survival. 91 In a study of 116 patients with ATTRwt amyloidosis, reduced serum TTR values were associated with short survival.…”
Section: Predictors Of Survivalmentioning
confidence: 99%
“…90 Survival was reduced if there was cardiac dysautonomia after LTX, or on MIBG-SPECT and no response to atropine. 91 In a study of 116 patients with ATTRwt amyloidosis, reduced serum TTR values were associated with short survival. 44 Low TTR serum levels were an independent predictor of the outcome in these patients.…”
Section: Predictors Of Survivalmentioning
confidence: 99%
“…As a result, insoluble amyloid fibrils accumulate in the peripheral and autonomic nerves, heart, gastrointestinal tract, kidneys, eyes, and connective tissues [1,2]. Three phenotypes predominate in ATTRv amyloidosis: one is almost exclusively characterized by restrictive cardiomyopathy, another predominantly by polyneuropathy (ATTR-PN), and the third is a mixed phenotype [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Among persons with the classic disease phenotype, death has been reported to occur within 10-15 years of symptom onset, often from cachexia and malnutrition due to gastrointestinal complications [11,12]. Prognostic survival factors include cardiac dysautonomia [3] and the presence of a mutation other than the more common Val30Met (also referred to as p.Val50Me) tgenotype [11,13]; both of which are associated with poorer survival.…”
Section: Introductionmentioning
confidence: 99%